2020
DOI: 10.1109/access.2020.3010031
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nonlinear Second Order Hyperbolic Partial Differential Equation-Based Image Restoration Algorithm With Directional Diffusion

Abstract: Recently, variational and partial differential equation (PDE)-based algorithms have become very important for image restoration. In this study, we propose a new second order hyperbolic PDE model based on directional diffusion for image restoration. This hyperbolic PDE restoration model can simply diffuse along the edge's tangential direction in the observed image, thereby removing noise while preserving the image edges and fine details, which avoids the staircase effect in the restored image. An effective nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…e results are shown in Figure 5. Grayscale value of the test set True value Method of [9] e proposed method It can be found that the proposed method has high consistency with the real value. In order to quantitatively evaluate the difference between the two methods, the concept of similarity rate is introduced here, which can be summarized as the ratio of similar samples to the total number of samples.…”
Section: Algorithm and Experimental Results Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…e results are shown in Figure 5. Grayscale value of the test set True value Method of [9] e proposed method It can be found that the proposed method has high consistency with the real value. In order to quantitatively evaluate the difference between the two methods, the concept of similarity rate is introduced here, which can be summarized as the ratio of similar samples to the total number of samples.…”
Section: Algorithm and Experimental Results Analysismentioning
confidence: 98%
“…Detailed restoration is performed on di erent image layers. Among the nontexture-based restoration methods, the more classical ones are the nonlinear partial di erential equation method [8,9] and the total variational restoration method [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tourist street view image information is the main source of all kinds of information that humans come into contact with. During the acquisition or transmission of tourist street view images, due to imaging principles, sensor defects, and changes in the surrounding environment, the signal may be unstable, and noises of different intensities may be generated, resulting in degradation of the tourist street view image quality [1]. Noise can be understood as interference signals that affect the acquisition or analysis of tourist street scene images from the signal source received by people or sensors.…”
Section: Introductionmentioning
confidence: 99%